1987
DOI: 10.1111/j.1528-1157.1987.tb03701.x
|View full text |Cite
|
Sign up to set email alerts
|

Double‐Blind Dose Reduction Study of Vigabatrin in Complex Partial Epilepsy

Abstract: Seventy-five epilepsy patients with at least two complex partial seizures/month were treated with gamma-vinyl GABA (GVG) 3 g/day for 3 months. Forty-one patients (54%) showed a reduction of greater than or equal to 50% in seizures. The median monthly seizure frequency decreased from 11.5 to 4 seizures/month. Twenty percent of patients had an improvement in general performance without a significant reduction in seizures. The responders entered the second phase of the study, in which 28 patients were randomly al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
47
0

Year Published

1989
1989
1999
1999

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 8 publications
(10 reference statements)
6
47
0
Order By: Relevance
“…In human epilepsy, GVG antagonizes seizures, especially those of focal onset, and apparently has relatively few side effects (Pedersen et al, 1985;Sivenius et al, 1987 In the present study GVG was administered to 21 patients in whom epilepsy was one manifestation of multiple, both anatomical and functional, cerebral defects. Other abnormalities were mental retardation, defects in communication, and motor and visual disturbances.…”
Section: Introduction Methodsmentioning
confidence: 86%
“…In human epilepsy, GVG antagonizes seizures, especially those of focal onset, and apparently has relatively few side effects (Pedersen et al, 1985;Sivenius et al, 1987 In the present study GVG was administered to 21 patients in whom epilepsy was one manifestation of multiple, both anatomical and functional, cerebral defects. Other abnormalities were mental retardation, defects in communication, and motor and visual disturbances.…”
Section: Introduction Methodsmentioning
confidence: 86%
“…Forty three patients entered the open phase of the trial, 23 from the placebo group and 20 from the vigabatrin treated group. On entering the open phase of the trial, seven of the 10 responders to vigabatrin continued the drug at 3 g/day; three withdrew, two to try other drug regimens, one for surgical assessment).…”
Section: Seizure Controlmentioning
confidence: 99%
“…Several groups have reported changes in subjectively assessed aggression, irritability, and other mood components, 3 20 21 but other studies have shown no effect of vigabatrin on mood'819 and an overall improvement in quality of life and subjective wellbeing as assessed by questionnaire. '8 [21][22][23] Methods…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Commonly reported side effects include drowsiness, dizziness, and mood changes (Rimmer and Richens, 1984;Sivenius et al, 1987;Tassinari et al, 1987;Matilainen et al, 1988; Mumford and Dam, 1989).…”
mentioning
confidence: 99%